1978
DOI: 10.1007/bf01875164
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the multi-pore system of alamethicin in a lipid membrane

Abstract: The electrical properties of an alamethicin multi-pore system have been studied by voltage-jump current-relaxation experiments (this paper) and by autocorrelation and spectral analysis (following paper). With these methods a slow time constant and a fast time constant were observed which differ by about one to three orders of magnitude depending on the experimental conditions. Steady-state current and time constants were analyzed as functions of voltage, alamethicin concentration and temperature. Within experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
86
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 39 publications
7
86
0
Order By: Relevance
“…As many as 20 distinguishable conductance states have been described (12). The fluctuations between the stepwise K þ and Cl À conductivities are consistent with the various sizes of the transmembrane channels due to the presence of different oligomeric states of the helix bundles (13,14) (reviewed in (1,2)). It has been suggested that these pore structures may consist of at least three (15), four (1), or even five subunits (16).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…As many as 20 distinguishable conductance states have been described (12). The fluctuations between the stepwise K þ and Cl À conductivities are consistent with the various sizes of the transmembrane channels due to the presence of different oligomeric states of the helix bundles (13,14) (reviewed in (1,2)). It has been suggested that these pore structures may consist of at least three (15), four (1), or even five subunits (16).…”
Section: Introductionmentioning
confidence: 62%
“…Magic-angle spinning (MAS) solid-state NMR techniques utilizing dipolar recoupling have been developed to measure distances between 13 C-isotopically labeled peptides, and the global structure can be reconstructed from the resulting data. However, most of these techniques yield only relatively short intermolecular distances (up to~5 Å ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of an electrical potential certain aggregates form membrane sprig chmels which are in a fast exchange with the monomer pool. Conclusive evidence for this mechanism was recently presented by Boheim and Kolb [2]. Jn most of these investigations both sides of the membrane contained equal amounts of peptide antibiotic.…”
mentioning
confidence: 84%
“…This discovery prompted elaborate studies in many laboratories, which resulted in a detailed concept for the ionophoric action of alamethicin and several analogues ( [2] covers the literature comprehensively). It was shown that alamethicin adsorbs to the membrane surface where monomers coexist with aggregates.…”
mentioning
confidence: 99%
“…It was reported several years ago (Menestrina et al, 1986) that even completely hydrophobic polypeptides of the type Boc-(AlaAib-Ala-Aib-Ala-),-OMe (Boc, t-butoxycarbonyl; Aib, aaminoisobutyric acid), which can adopt a straight transmembrane helical structure, induce voltage-dependent ionic conductance across planar lipid bilayers, but it was not possible in this particular case to observe the low-conductance states observed with the structurally related peptide antibiotic alamethicin (Boheim and Kolb, 1978;Hanke and Boheim, 1980). How can one change the sequence of these simple peptides in order to realize stable membrane channels?…”
mentioning
confidence: 96%